A Phenytoin Induced Toxic Epidermal Necrolysis (TEN) – A Case Report - NVS, Mounica; C, Vyuha; K, Sahithi; B, Roopa; S, Ponnusankar (Indian Journal of Pharmacy Practice)
Toxic Epidermal Necrolysis (TEN) is a rare, potentially life threatening dermatological condition that is usually induced by medications. The usage of anticonvulsants like carbamazepine, phenytoin, lamotrigine, phenobarbital, fosphenytoin are associated with high risk for occurrence of TEN. A 36 year old female patient was brought with the history of Phenytoin induced Toxic Epidermal Necrolysis. This patient was prescribed tablet phenytoin 300mg/day, 100mg in the morning and 200mg at night for her generalized tonic-clonic seizure disorder and patient had history of using the drug for a period of 28 days. Patient developed macular rashes on the skin and consulted a general physician who prescribed her with cetirizine 5mg, bid. The drug phenytoin was continued till she visited Government District Head Quarters Hospital,Udhagamandalam in spite of treatment with cetirizine the rashes spread all over the body with an additional ocular redness with discharge. This case report describes the management of this patient.
Keywords: Toxic epidermal necrolysis; phenytoin; tonic-clonic seizures; anti-convulsants